Feasibility study of preoperative microvessel evaluation and characterization in perforator flaps using various modes of color‐coded duplex sonography (CCDS). Issue 7 (15th September 2020) - Kehrer, Andreas; Lonic, Daniel; Heidekrueger, Paul; Bosselmann, Talia; Taeger, Christian D.; Lamby, Philipp; Kehrer, Michael; Jung, Ernst Michael; Prantl, Lukas; Platz Batista da Silva, Natascha
Abstract: Background: Color‐coded duplex sonography (CCDS) is useful for perforator flap design showing the highest sensitivity in identifying microvessels. This prospective study evaluates the feasibility of different ultrasound (US) modes applied by the microsurgeon in daily practice suggesting quantifiable reference values. Methods: Twenty‐four patients aged between 17 and 68 years (mean 43.3 ± 14.2 years) with 18 anterolateral thigh (ALT) and 6 superficial circumflex iliac artery (SCIP) flaps were included. Indications were traumatic ( n = 12), infectious ( n = 6), ischemic ( n = 4), or tumor‐associated defects ( n = 2). Different US modes were evaluated regarding applicability using multifrequency linear probes (5–15 MHz). Vessels diameter, peak systolic velocity (PSV), end diastolic velocity (EDV), and resistance index (RI) were measured. Preoperative results were correlated to intraoperative findings. Results: In the examined patient group with 24 perforator flaps a 100% correlation was seen when comparing perforators detected with CCDS/PD with intraoperative findings using optimized US settings. Sensitivity, PPV, and accuracy of CCDS were 100% respectively. Mean PSV of 16.99 ± 6.07 cm/s, mean EDV of 5.01 ± 1.84 cm/s and RI of 0.7 ± 0.07 were measured in microvessels (PW‐mode). CCDS proved to be superior compared to PD in correct diameter assessment showing a mean diameter of 1.65 ± 0.45 mm, compared to PD‐mode 1.31 ± 0.24 mm. Mean PSV and EDV were higher in ALT than in SCIP flaps, RI was slightly higher in SCIP flaps ( p  > .05). There were no significant differences in size of different flaps' perforators ( p  > .05). Conclusion: CCDS represents a highly valuable tool in the daily practice of free flap reconstructions using optimized low flow US settings and multifrequency linear probes.